Answer:
2.125
Step-by-step explanation:
Answer:
7/12
Step-by-step explanation:
The nth term Tₙ = n(n-4) /n+3.
The 1st term T₁ = 1(1 - 4)/(1 + 3) = -3/4
The 6th term T₆ = 6(6 - 4)/(6 + 3) = 6(2)/9 = 2(2)/3 = 4/3
So, the sum of the 1st and 6th terms is T₁ + T₆ = -3/4 + 4/3
= (-9 + 16)/12
= 7/12
It depends on how you count them. If you describe them by their dimensions, lowest one first, you can have
1 x 1 x 18
1 x 2 x 9
1 x 3 x 6
2 x 3 x 3
Of course, these dimensions can be put in any order.
Answer:
0
Step-by-step explanation:
Cancel out x-y to x^2-Y^2 and you get x+y-x-y which is 0